Sustainability reporting strategy in universities - Sudaryati, Dwi (Advances in business related scientific research journal, 2025)
This research is concerned with universities as agents of change in achieving sustainable development goals. Universities have great potential to contribute to sustainability through their innovations and programs. Sustainability reporting is one form of conveying information about universities’ sustainability contributions. This study aims to analyze the relationship between university rank, region, and university size among 685 universities in Asia that participated in the UI GreenMetric during the 2022– 2023 period, totaling 1,273 observations. The data were analyzed using regression analysis. The results indicate that university rank and region significantly influence sustainability reporting and that university size does not. This suggests that universities are strongly influenced by external factors, such as rankings and regional considerations, when reporting their sustainability contributions to fulfill the demands of external stakeholders. This research is useful in determining sustainability reporting policies for universities in the Asian region.
Keywords: campus type; ranking; region; sustainability reporting